2017
DOI: 10.1111/febs.14140
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of a hyperthermophilic thymidylate kinase enzyme reveal conformational substates along the reaction coordinate

Abstract: Structural data are available in the PDB under the accession numbers 2PBR, 4S2E, 5H5B, 5XAI, 4S35, 5XB2, 5H56, 5XB3, 5H5K, 5XB5, and 5XBH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Thus, the binding of both of the substrates at the active site would be random in sequence and will follow a random bi-bi mechanism for substrate binding. A similar mode of substrate binding was also observed in a close homologue, A. aeolicus TMPK (Biswas, Shukla, Chaudhary et al, 2017). This is further reinforced by studies on mouse TMPK, adenylate kinase and guanylate kinase (Cheng & Prusoff, 1973;Sheng et al, 1999;Li et al, 1996).…”
Section: Insight Into the Mode Of Substrate Binding From The Crystal supporting
confidence: 64%
See 1 more Smart Citation
“…Thus, the binding of both of the substrates at the active site would be random in sequence and will follow a random bi-bi mechanism for substrate binding. A similar mode of substrate binding was also observed in a close homologue, A. aeolicus TMPK (Biswas, Shukla, Chaudhary et al, 2017). This is further reinforced by studies on mouse TMPK, adenylate kinase and guanylate kinase (Cheng & Prusoff, 1973;Sheng et al, 1999;Li et al, 1996).…”
Section: Insight Into the Mode Of Substrate Binding From The Crystal supporting
confidence: 64%
“…Thus, Arg91 acts as a hub for suboptimal paths that connect ATP and TMP at the active site. Biochemical studies of TMPK from other organisms have shown that mutation of the residues (Arg91, Asp12 or Tyr99) leads to a loss of enzyme activity (Biswas, Shukla, Chaudhary et al, 2017;. The agreement between the network analysis and the experimental results from earlier studies motivated us to explore the roles of the residues found in the suboptimal paths between ATP and TMP.…”
Section: Trajectory and Network Analysis Of The Tttmpk-atp-mg 2+ -Tmpmentioning
confidence: 77%
“…Investigation and resolution of residue interaction network (RIN) is imperative for the understanding protein structure-function relationships (Amitai et al, 2004 ; Del et al, 2006 ; Vishveshwara et al, 2009 ). Recently, RIN analysis has been successfully applied to investigate mutation effects, protein folding, domain-domain communication, and catalytic activity (Dokholyan et al, 2002 ; Swintkruse, 2004 ; Del et al, 2006 ; Soundararajan et al, 2010 ; Boehr et al, 2013 ; Scaini et al, 2014 ; Biswas et al, 2017 ). Based on the interaction mode analysis, we found that 1,5-InsP 8 lost some interactions and formed novel interactions with the jasmonate receptor complex in different systems.…”
Section: Resultsmentioning
confidence: 99%
“…Other significant perturbations to urinary metabolites appear to involve nucleotides, specifically increased monophosphate nucleotides (AMP, UMP, IMP) and decreased diphosphate nucleotides (GDP, CDP) in RSV samples. Monophosphate nucleotides are converted to diphosphate nucleotides by nucleoside-monophosphate kinases (NMPK) [30], while the opposite conversion from diphosphate to monophosphate nucleotides is mediated by nucleoside pyrophosphatase/phosphodiesterases (NPPs) [31]. Hence, accumulation of monophosphate nucleotides and decrease in diphosphate nucleotides may be due to either decreased NMPK activity, and/or increased NPP activity in urine-associated tissues such as the kidney or urinary tract.…”
Section: Discussionmentioning
confidence: 99%